2018
DOI: 10.1109/twc.2018.2819188
|View full text |Cite
|
Sign up to set email alerts
|

Symbol Detection of Ambient Backscatter Systems With Manchester Coding

Abstract: Ambient backscatter communication is a newly emerged paradigm, which utilizes the ambient radio frequency (RF) signal as the carrier to reduce the system battery requirement, and is regarded as a promising solution for enabling large scale deployment of future Internet of Things (IoT) networks.The key issue of ambient backscatter communication systems is how to perform reliable detection. In this paper, we propose novel encoding methods at the information tag, and devise the corresponding symbol detection meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 28 publications
(69 reference statements)
0
39
0
Order By: Relevance
“…Similarly, a flicker detector uses per symbol in-band BackCom while using a residual channel of WiFi packets [87]. Tao et al suggested a semi-coherent manchester detector and a non-coherent manchester detector [88]. These detectors could decode the manchester-coded and differential manchester-coded information, respectively.…”
Section: Decision Regions For Joint Energy Detectormentioning
confidence: 99%
“…Similarly, a flicker detector uses per symbol in-band BackCom while using a residual channel of WiFi packets [87]. Tao et al suggested a semi-coherent manchester detector and a non-coherent manchester detector [88]. These detectors could decode the manchester-coded and differential manchester-coded information, respectively.…”
Section: Decision Regions For Joint Energy Detectormentioning
confidence: 99%
“…where I m (a) is the modified Bessel function of the first kind [43]. For small σ 2 w values, we may use the approximation I m (a) ≈ e a and rewrite (26)…”
Section: Suboptimal Energy Detector For On-off-keying Backscattermentioning
confidence: 99%
“…A noncoherent detection strategy for bistatic scatter radio is devised in [8]. Increasing the complexity of the tag, use of differential coding has been considered for AmBC systems in [26], [27], and semi-coherent and noncoherent detection approaches are examined. At high SNR and for large data samples available at the reader, a noncoherent detector is proposed in [28].…”
Section: Introductionmentioning
confidence: 99%
“…Ambient backscatter communication using orthogonal frequency division multiplexing (OFDM) is investigated in [14], [15]. On the same lines, [16], [17] explored new coding schemes, such as Manchester coding, to improve detection performance.…”
Section: A Related Workmentioning
confidence: 99%